The Street Vendors Perception to the Information of Public Access Disruption as the Effect of their Existence - Yadewani, Dorris; ., Syafrani (International Journal of Engineering and Technology, 2018)
Street vendors is a phenomenon in almost all regions in Indonesia, which is always a positive and negative impact on the region where the street vendor activity. The positive is the economy in a sustainable life in areas where street vendor activities, while the negative effects are disturbed some public access as a result of the existence of such street vendor, such as public roads are always jammed, the sidewalk is not functioning, trash increases or the environment increasingly neglected, area aesthetics will show discomfort. For the more crowded street vendor activities will have an impact upon the producer. However street vendor unaware that what was done to give effect to society because of disruption of public facilities. It is very necessary of information for the  street vendor’s understanding and perception to the impact caused by their presence in an area. The research was conducted by qualitative method with type research field investigations and descriptive analysis of the street vendor, managers, buyers and decision makers who do trading activities in S. Parman Street, UlakKarang Padang.  Samples as research subjects were the street vendors as much as 5 people, managers, local government, the buyer and road users. The data used are primary data and secondary data. Data Collection Techniques conducted by observation, interview, and documentation while data analysis is conducted qualitatively by a descriptive approach. The findings and the results are show that the information obtained is correct in running its activities to seek fortune already utilizing public access such as sidewalk and road. Contributions to the street vendors are expected to have awareness in running its activities mainly on the utilization of public access and if you want to keep running its activities must be willing to abide by all the regulations set forth by the government, because it became a street vendor answers to some of the problems faced by street vendors as well as for the government attempted to manage and regulate the existence of street vendors to be in line with policies that have been set by the government for street vendors somehow able to overcome the problem of the existence of the public economy.
Keywords: Street vendors; public facilities; government policies.